PESTS INTENSITY IN POTATO (Solanum tuberosum) AND FABA BEAN (Vicia faba) INTERCROPPING IN SALARAN, GETASAN DISTRICT, SEMARANG REGENCY - Setiawan, Andree Wijaya; Simanjuntak, Bistok Hasiholan; Andhika, Gideon Febby Prima (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
Tropical regions face threats from pests, leading to significant losses in the global potato supply. Intercropping potatoes with faba beans is being explored to control pest infestations in tropical areas. This study aims to provide insights into pest dynamics and improve pestmanagement strategies for sustainable potato cultivation. The research evaluates five cropping systems, each replicated across seven beds: potato monoculture, alternating growth of potatoes and faba beans at a 2:1 ratio, planting faba beans between the rows of potatoes at a 1:1 ratio, growing faba beans between two beds of potatoes, and cultivating solely faba beans. The study looked at various factors such as the type and intensity of pest attacks on potatoes. It found that planting faba beans alongside potatoes can help reduce aphid (Homoptera: Aphididae) and mirid bug (Hemipetra: Miridae) attacks, but may not affect grasshopper (Orthoptera: Acrididaeand Pyrgomorphidae) attacks. The distance between potato beds and the population of faba bean plants can also influence pest interactions. Understanding these dynamics offers important information for sustainable pest management practices in intercropping systems.